Dynamic performance and sensitivity of grid-connected hydropower station under uncertain disturbance. Issue 1 (1st September 2022) - Liu, Y; Guo, W C; Cao, R; Chen, Z; Wang, L
Abstract: The grid-connected operating condition of hydropower station is a common operation mode to provide electric energy for the load side. This paper investigates the dynamic performance and sensitivity of grid-connected hydropower station (GCHS) under uncertain disturbance. Firstly, the nonlinear uncertain model of GCHS under uncertain disturbance is established. Then, the dynamic performance of GCHS is studied when the governor parameters change under certain step disturbance, periodic disturbance and uncertain random disturbance, respectively. Finally, based on the sensitivity index of the uncertain output obtained from the extended Fourier amplitude sensitivity test method, the sensitivity of the uncertain random disturbance at different input positions is studied. The results indicate that the GCHS under periodic disturbances or random disturbances have more complex dynamic performance than that under certain step disturbance. Under periodic disturbance, the forced oscillations and high frequency resonances are generated in dynamic response of GCHS. Under the uncertain random disturbance, the system of GCHS always presents random oscillation. The state variables q H, z, qP, y, x s, x t, and δ of GCHS are the most sensitive to uncertain disturbances, which are introduced at the generator or surge tank. The uncertain disturbances have significant interaction on the dynamic response of GCHS.